Identificação das áreas aptas a aplicação de biofertilizantes suínos com utilização de SIG - Silva, Jefferson Luiz Gonçalves (2017)
Brazil is the fourth largest swine producer and exporter in world, with swine farming being very representative in the national scenario. This production, however, implies generation of waste and this needs to be mitigated. One of the alternatives to reduce the impact caused by pig waste is the application of anaerobic biodigestion treatment, obtaining biogas and digestate as by-products. Digestate can be used as biofertilizer, generating a new product. In this context, this work proposes to define a geographic database from different sources about the national production of swine and to estimate, supported by calculation methodology defined in activities of the BiogasFert Network, the respective production of waste and biogas. These results were provided in an web system using GeoServer map server. In addition, a methodology was defined in this work to identify areas of permanent preservation in top of hills, based on the Brazilian new forest code published since 2012, and in classes of declivity unfit for fertilizer inputs (regions with slopes greater than 45%). As result, a total of 60,879,431 km² (0,72%) of areas considered inapt for the application of fertilizers in the national territory were identified. Another objective of this work was to highlight the use of free GIS software and its processing power, since the metrics applied here were elaborated using exclusively open source software.